Comparison of Myocardial Perfusion Scintigraphy and Computed Tomography (CT) Angiography Based on Coronary Angiography - Tasdemir, B.; Balci, T. A.; Demirel, B. B.; Karaca, I.; Aydin, A. M. (Springer, 2010)
[Abstract Not Available]
23rd Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 09-13, 2010 -- Vienna, AUSTRIA